Computers and devices for communication proceedings of CODEC 2019 ; Calcutta, India, 19-20 December 2019 - Das, Nikhil Ranjan; Sarkar, Santu (Singapore Springer, 2021)
This book gathers selected research papers presented at the 7th International Conference on Computers and Devices for Communication (CODEC 2019), held at the Department of Radio Physics and Electronic, University of Calcutta, India, on 19 – 20 December 2019. It includes recent research in the field of nanomaterials, devices and circuits; microwave and light wave technology; communication and space science; and computer applications and control.
Electronic reproduction
Keywords: Telecommunication -- Congresses